Strengthening Brand Image through Integrated Marketing Communication: A Case Study of Sekolah Kak Seto's Approach to Educational Service Marketing - Tiara, Shofi; Dian Fordian (SKeTsa Bisnis (e-jurnal), 2025)
Introduction: This study aims to analyze the marketing communication strategies implemented by Sekolah Kak Seto in an effort to enhance the institution's brand image. The research is motivated by the growing importance of integrated marketing communication in shaping a positive public perception of educational institutions, particularly amid increasingly competitive conditions. The research question formulated is: "How does Sekolah Kak Seto implement marketing communication strategies to improve its brand image?". Methods: This study employs a descriptive qualitative method, with data collected through interviews, observations, and literature reviews. Results: The findings indicate that the strategies applied are based on the Integrated Marketing Communication (IMC) framework, which includes advertising, sales promotion, public relations, personal selling, and direct marketing. Conclusion: These strategies have been proven to positively impact the enhancement of the brand image and the overall growth of Sekolah Kak Seto.